"That's really clever!" Ironic hyperbole understanding in children*. Issue 1 (2nd May 2017) - AGUERT, MARC; LE VALLOIS, CORALIE; MARTEL, KARINE; LAVAL, VIRGINIE
Abstract: Hyperbole supports irony comprehension in adults by heightening the contrast between what is said and the actual situation. Because young children do not perceive the communication situation as a whole, but rather give precedence to either the utterance or the context, we predicted that hyperbole would reduce irony comprehension in six-year-olds ( n = 40) by overemphasizing what was said. By contrast, ten-year-olds ( n = 40) would benefit from hyperbole in the way that adults do, as they would perceive the utterance and context as a whole, highlighted by the speaker's ironic intent. Short animated cartoons featuring ironic criticisms were shown to participants. We assessed comprehension of the speaker's belief and speaker's intent. Results supported our predictions. The development of mentalization during school years and its impact on the development of irony comprehension is discussed.